The Economics of Geographical Indications - Daniela Benavente (Graduate Institute Publications, 2013)
This book seeks to contribute to an understanding of the role played by international trade law in shaping economic outcomes from a theoretical perspective. The focus is on geographical indications (GI), an intellectual property right defined in the TRIPs Agreement of the WTO. The premise is that a GI can be conceptualized as a 'club asset': firms that produce GI-labelled goods both add value and derive benefits from the GI. The book starts by presenting a dynamic model of GI reputation under...